Conceptualizing Open Data ecosystems: A timeline analysis of Open Data development in the UK - Maximilian Heimstädt; Fredric Saunderson; Tom Heath (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2014)
In this paper, we conceptualize Open Data ecosystems by analysing the major stakeholders in the UK. The conceptualization is based on a review of popular Open Data definitions and business ecosystem theories, which we applied to empirical data using a timeline analysis. Our work is informed by a combination of discourse analysis and in-depth interviews, undertaken during the summer of 2013. Drawing on the UK as a best practice example, we identify a set of structural business ecosystem properties: circular flow of resources, sustainability, demand that encourages supply, and dependence developing between suppliers, intermediaries, and users. However, significant gaps and shortcomings are found to remain. Most prominently, demand is not yet fully encouraging supply and actors have yet to experience fully mutual interdependence.
Keywords: 650; Open Data ecosystem; Open Government Data; framework; United Kingdom